Civil Society as Peacebuilder in the Internet Era - Edwin Prasetiawan; Arofatin Maulina Ulfa (Global South Review, 2015)
Peace building in the modern era is different from those in the World War era. While the latter focused more on the state-to-state policy, the former involves the participation of the society. Part of the explanation is the fast growing development of information and technology, particularly the development of internet, which has helped providing more spaces for civil society to involve and to influence peace building process in any humanitarian activities. This space, as manifested in various social media such as Facebook and Twitter, has become a new way for the so-called netizen (internet citizen) to access information on the existing conflicts, advocate or campaign for the management and settlement of the conflicts, gather financial supports for the peace building process, and develop confidence building among people of the conflicting parties. However, at the same time this space may jeopardize the peace building process as people has no restriction in expressing their opinion online which could deteriorate the relations among people from both sides. This paper, therefore, aims to examine the role of this online activism to peace building process in various cases.